BURNOUT DITINJAU DARI DUKUNGAN SOSIAL PADA PERAWAT RUMAH SAKIT UMUM PERMATA BUNDA MEDAN - Wynona Christie Ong (Jurnal Psikologi Universitas HKBP Nommensen, 2020)
This study aims to find out the relationship between social support and burnout. The hypothesis proposed in this study states that there is a negative relationship between social support and burnout, assuming that the higher is social support, the lower burnout will be and conversely the lower is the social support, the higher will the burnout be. The subjects of this study were 150 nurse of General Hospital Permata Bunda Medan. Data were obtained from a scale to measure social support and burnout. The calculation was performed by testing requirements analysis (assumption test), which consisting of normality test and linearity test. Data analysis was performed by using Product Moment Correlation Analysis through SPSS 17 for Windows. The results of data analysis showed that r = -0.581; and p = 0.000 (p < 0.05), which indicates that there is a negative relationship between social support and burnout. The results of this study indicate that the contributions made by the variable of social support on burnout is 33.8 percent, while the remaining 66.2 percent is influenced by other factors not examined in this study. From these results, it is concluded that the hypothesis stating that there is a negative relationship between social support and burnout.